PENGARUH DISIPLIN, LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI UNIT PELAKSANA PELAYANAN TERPADU SATU PINTU (UP PTSP) WILAYAH KOTA ADMINISTRASI JAKARTA BARAT - Tetuko, Eka Herma; Soehari, Tjiptogoro Dinarjo (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aims to examine and analyze the effect of discipline on employee performance, the effect of work environment on employee performance, the effect of leadership style on employee performance at Unit Pelaksana Pelayanan Terpadu Satu Pintu (UP PTSP) Wilayah Kota Administrasi Jakarta Barat and the effect of discipline, work environment and leadership style simultaneously on employees performance at UP PTSP Wilayah Kota Administrasi Jakarta Barat. The sampling method used was simple random sampling. From a population of 210 Pegawai Negeri Sipil (PNS), 138 PNS met the criteria to be the sample. The method of analysis used in this study is multiple linear regression. The results showed discipline, work environment, and leadership style simultaneously are having significant effect on employee performance. Partially discipline and leadership style have a significant positive effect on employee performance, while the work environment has positive but not significant effect on employee performance. Leadership style is the variable of the greatest effect on employee performance